Some Improved q-Rung Orthopair Fuzzy Aggregation Operators and Their Applications to Multiattribute Group Decision-Making. (27th December 2019) - Xu, Lei; Liu, Yi; Liu, Haobin
Abstract : As a generalization of intuitionistic fuzzy set (IFS) and Pythagorean fuzzy set (PFS), q -rung orthopair fuzzy set ( q -ROFS) is a new concept in describing complex fuzzy uncertainty information. The present work focuses on the multiattribute group decision-making (MAGDM) approach under the q -rung orthopair fuzzy information. To begin with, some drawbacks of the existing MAGDM methods based on aggregation operators (AOs) are firstly analyzed. In addition, some improved operational laws put forward to overcome the drawbacks along with some properties of the operational law are proved. Thirdly, we put forward the improved q -rung orthopair fuzzy-weighted averaging ( q -IROFWA) aggregation operator and improved q -rung orthopair fuzzy-weighted power averaging ( q -IROFWPA) aggregation operator and present some of their properties. Then, based on the q -IROFWA operator and q -IROFWPA operator, we proposed a new method to deal with MAGDM problems under the fuzzy environment. Finally, some numerical examples are provided to illustrate the feasibility and validity of the proposed method.